THE IMPACT OF DEMOGRAPHIC TRANSITION ON TAX REVENUE IN INDONESIA - Effendi, Yuventus; Hidayat, Wahyu; Nurwanda, Asep (Scientax, 2019)
In the next few decades, Indonesia will experience significant demographic transition such as increasing productive age cohort and ageing populations. This study aims to construct a framework to analyze the nexus between demographic transition, Indonesian economy, and the state budget. This study uses 3Ps (productivity, proportion, and participation) model as a basic framework. Further, this paper differentiates between demographic related tax revenue and non-demographic. We find that productivity is the main engine of the economic growth in both historical data points and in our future projection. Also, ageing populations would hamper the economy in the future through lower productivity. Hence in the short run, taxation agenda should focus on extending tax base to capture the demographic transition. In the long run, maintaining taxpayers to keep paying tax properly is an appropriate strategy. These could be done by early tax education and transparency in managing tax revenue.